Thermodynamic and electrochemical investigation of (9-[(R) 2[[bis [[(isopropoxycarbonyl)oxy]methoxy] phosphinyl] methoxy] propyl] adenine fumarate) as green corrosion inhibitor for mild steel in 1M HCl - Shahi G.; Verma C.B.; Ebenso E.E.; Quraishi M.A. (My University, 2025)
Corrosion inhibition property of [(9-[(R) 2 [[bis [[(isopropoxycarbonyl) oxy] methoxy] phosphinyl] methoxy] propyl] adenine fumarate)] (Tenvir) on mild steel in 1M HCl have been investigated using chemical and electrochemical methods. The Tenvir acts as efficient corrosion inhibitor for mild steel in 1M HCl and its inhibition efficiency increases on increasing concentration. Potentiodynamic polarization study revealed that Tenvir effectively suppressed both the anodic and cathodic processes of mild steel corrosion in acid solution and behaves as mixed-type inhibitor. Formation of the protective film of this Tenvir on mild steel surface was studied by Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) techniques. Adsorption of the Tenvir on the mild steel surface in acid solution was found to obey the Langmuir adsorption isotherm. Effect of temperature on the inhibition efficiency was also investigated and some thermodynamic parameters were calculated in order to explain the mechanism of adsorption. © 2015 The Authors.